3D Printing Technologies - Bernasconi, Roberto (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The family of technologies collectively known as additive manufacturing (AM) technologies, and often called 3D-printing technologies, is rapidly revolutionizing industrial production. AM's potential to produce intricate and customized parts starting from a digital 3D model makes it one of the main pillars for the forthcoming Industry 4.0. Thanks to its advantages over traditional manufacturing methodologies, AM finds potential applicability in virtually all production fields. As a natural consequence of this, research in this field is primarily focused on the development of novel materials and techniques for 3D printing. This Special Issue of Technologies, titled "3D Printing Technologies", aims at promoting the latest knowledge in materials, processes, and applications for AM. It is composed of six contributions, authored by influential scientists in the field of advanced 3D printing. The intended audience includes professors, graduate students, researchers, engineers and specialists working in the field of AM.